The Effect of Leverage and Tax Avoidance on Earnings Management in Cement Manufacturing Companies Listed on the Indonesia Stock Exchange in 2020–2024 - Azizah, Ghina; Eimar, Cut Rachel; Aulia, Syahirah Chanda; Ningrum, Cahaya; Dawolo, Kristiani; Ramadhan, Ramadhan; Mahwiyah, Mahwiyah (Jurnal Multidisiplin Sahombu, 2025)
This study aims to examine the influence of leverage and tax avoidance, both individually and jointly, on earnings management among companies listed on the Indonesia Stock Exchange. Using a quantitative descriptive analysis approach, the findings indicate that leverage has a significant and positive effect on earnings management, suggesting that companies with higher debt levels are more likely to engage in income manipulation. Similarly, tax avoidance also shows a significant and positive impact on earnings management, reflecting the tendency of firms to adjust reported income to reduce tax liabilities. The panel regression analysis further confirms that leverage and tax avoidance collectively affect earnings management, with the probability value supporting the conclusion that both variables are statistically significant determinants of earnings manipulation practices in the manufacturing sector.